Counseling Close to Home: Genetic Counselors' Experiences with their own Family Members. Issue 1 (16th August 2017) - Rust, Laura; Adamsheck, Hallee; Reiser, Catherine A.; Petty, Elizabeth M.
Abstract: Genetic counselors are trained to provide personalized genetic information and support to clients and their families. When requests for counseling comes from the counselor's own family member, should that counselor still provide service? There is a paucity of literature regarding genetic counselors counseling their own family members and no specific recommendations regarding how to reply to requests for genetic information from relatives. The purpose of this mixed methods study was to report genetic counselors' and genetic counseling students' perspectives and experiences providing genetic counseling to relatives. In the present study, 423 genetic counselors and genetic counseling students completed a 70‐item web‐based survey that explored genetic counselors' experiences counseling family members outside of a clinic setting. The majority (73%; n = 301/410) of respondents have been asked to provide genetic counseling. Over half (57%; n = 257/423) provided counseling, personalized genetic information or risk assessment to family members. Only a small fraction of respondents (11%; n = 45/420) responded that they received any formal training in their graduate education, or in any other capacity that addressed the issue of how genetic counselors should respond to genetic counseling requests made family members. Those who have were less likely to provide genetic counseling to a family member (p < 0.05) . Respondents who provided genetic counseling to relatives were significantly more likely to think their colleagues would do the same. Those who never provided genetic counseling to relatives were more likely to think their colleagues would refer to an unrelated genetic counselor (p < 0.0001). We highlight how our results have clinical and professional implications and provide suggestions to generate discussion among genetic counselors on how they might respond to requests for counseling from family members.